1992
DOI: 10.1177/089826439200400402
|View full text |Cite
|
Sign up to set email alerts
|

Age at Migration, Social Connections, and Well-Being among Elderly Hispanics

Abstract: This study employs data from the 1988 National Survey of Hispanic Elderly People to examine the impact of age at migration and social contacts on the self-assessed health, functional disability, and life satisfaction of elderly Cuban Americans, Mexican Americans, and Puerto Ricans in the United States. The results indicate that the difficulties associated with immigration late in life undermine an older person's morale and interfere with the ability to perform basic activities of daily living. Although childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 22 publications
5
86
0
4
Order By: Relevance
“…Indeed, CA have been shown to dier from other Hispanic groups on factors such as education (Angel and Angel, 1992) and utilization of health care services (Schur et al, 1987). This group has also been shown to report better health, less physical disability and higher life satisfaction in relation to other elderly Hispanic groups (Angel and Angel, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, CA have been shown to dier from other Hispanic groups on factors such as education (Angel and Angel, 1992) and utilization of health care services (Schur et al, 1987). This group has also been shown to report better health, less physical disability and higher life satisfaction in relation to other elderly Hispanic groups (Angel and Angel, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have looked beyond nativity to examine the effect of migration differences, such as age of arrival to the U.S. and length of U.S. residence on the mental health of Latino immigrants (J. Angel & Angel, 1992;Mills & Henretta, 2001;Portes & Rumbaut, 2001;Singh & Siahpush, 2001;Vega & Gil, 1998;Vega et al, 2002;Vega, Sribney, Aguilar-Gaxiola, & Kolody, 2004;Warheit, Vega, Khoury, & Gil, 1996). These findings provide a more complicated picture of the immigrant experience and indicate that factors beyond nativity contribute to the risk of poor mental health.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mills and Henretta (Mills & Henretta, 2001) found that immigrants who came to the U.S. after age 35 were more depressed than those arriving at an earlier age. Other studies have indicated that difficulties associated with immigration late in life, such as low English language acquisition and social isolation, may undermine an older person's morale, leading to augmented risk for illness and dysfunction (Angel & Angel, 1992;Angel, Angel, Geum-Yong, & Markides, 1999).In addition, isolation from the mainstream culture may also prevent older immigrants from serving as protective agents and mediators for their children's interactions with harmful aspects of U.S. culture (Berry, 1998;Elder et al, 2005). This may and actually lead to role reversals, where their children take a more authoritative role and erode the affiliative obedience and respect for the adults (Zhou, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Esta divergencia podemos atribuirla en parte a las diversas poblaciones de las que se ha derivado cada clasificación, ya que el desplazamiento internacional experimentado por los participantes en nuestro estudio supone la ruptura -al menos temporalmente-con los vínculos familiares, y, en consecuencia, recurrir al grupo de iguales disponible -generalmente otros compatriotas emigrantes-es la primera y más habitual vía de reconstrucción de la red. Si bien el examen de Litwin también se realizó con inmigrantes rusos en Israel, consistió en una muestra de ancianos, por lo que es más probable que contasen con antecedentes familiares en el país de destino (Angel y Angel, 1992;Bialik-Gilad, 1988;Die y Seelbach, 1988;Ikels, 1986) y, por tanto, que entrasen a formar parte desde el primer momento de reasentamiento de sus redes sociales.…”
Section: Discussionunclassified